Old Sea, New Ice: sea ice geoengineering and indigenous rights in Arctic Ocean governance - Chuffart, Romain; Cooper, Aaron Martin; Wood-Donnelly, Corine; Seddon, Laura (The Polar Journal, 2023)
This comprehensive paper explores the complex interplay between Arctic sea ice governance, geoengineering, and the rights of Indigenous peoples. It raises critical questions about the feasibility of regulating potential sea ice geoengineering initiatives while upholding Indigenous rights. Employing a multidisciplinary approach, the paper investigates diverse perspectives on Arctic sea ice encompassing its roles in climate science, international law, and for Arctic Indigenous peoples, contributing to ongoing discussions on implementing Indigenous rights within Arctic governance and emerging climate technologies. As climate interventions are becoming a likely reality, the paper emphasises the imperative of integrating marine geoengineering responses to climate change into global ocean law and governance, with a specific focus on climate justice and the active involvement of Indigenous and local communities in the decision-making. Using analogies of resource exploitation, this paper also explores whether the conceptualisation of geo-engineered sea ice as a resource and looking at existing international legal frameworks governing resource extraction could enhance the effective implementation of Indigenous rights. The paper contends that there is an urgent need to develop an oceanic ethics component that considers Indigenous rights in the context of geoengineering, and advocates for nature-centric visions, Indigenous-led climate actions, and community-level marine resource management within international legal frameworks to strike a balance between the rights-based approach and emerging climate intervention technologies. publishedVersion